Knockdown of SNHG14 Alleviates MPP+-Induced Injury in the Cell Model of Parkinson’s Disease by Targeting the miR-214-3p/KLF4 Axis - Zhou, Shufang; Zhang, Dan; Guo, Junnan; Zhang, Junshi; Chen, Yong (Frontiers in Neuroscience, 2020)
Background Parkinson’s disease (PD) is the second most common neurodegenerative disease. Long non-coding RNA (lncRNA) small nucleolar RNA host gene 14 (SNHG14) has been demonstrated as an important regulator in PD pathology. However, the functional mechanisms played by SNHG14 in PD remain largely unclear. Methods We used 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and 1-methyl-4-phenylpyridinium (MPP+) to establish PD mouse and cell models. The levels of SNHG14, miR-214-3p, and Krüppel-like factor 4 (KLF4) were gauged by quantitative real-time polymerase chain reaction (qRT-PCR) or western blot analysis. Cell viability and apoptosis were determined using the Cell Counting-8 Kit (CCK-8) assay and flow cytometry, respectively. The levels of inflammatory cytokines were evaluated by ELISA. The relationships among SNHG14, miR-214-3p, and KLF4 were confirmed by dual-luciferase reporter and RNA immunoprecipitation (RIP) assays. Results Our data indicated that SNHG14 was upregulated and miR-214-3p was downregulated in PD models. SNHG14 knockdown ameliorated MPP+-stimulated damage in SK-N-SH cells, as evidenced by the enhancement in cell viability and the suppression in cell apoptosis and pro-inflammatory cytokine production. Mechanistically, SNHG14 directly targeted miR-214-3p via binding to miR-214-3p, and SNHG14 knockdown protected SK-N-SH cell from MPP+-stimulated cytotoxicity by upregulating miR-214-3p. KLF4 was a direct target of miR-214-3p, and SNHG14 regulated KLF4 expression by acting as a miR-214-3p sponge. Furthermore, miR-214-3p overexpression alleviated MPP+-stimulated damage in SK-N-SH cells by downregulating KLF4. Conclusion Our current study first demonstrated the protective effect of SNHG14 knockdown on MPP+-stimulated cytotoxicity in SK-N-SH cells at least partially by targeting the miR-214-3p/KLF4 axis, illuminating a promising target for PD intervention and treatment.